2014
DOI: 10.1016/j.bbagrm.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

SRSF2 promotes splicing and transcription of exon 11 included isoform in Ron proto-oncogene

Abstract: The product of proto-oncogene Ron is a human receptor for the macrophage-stimulating protein (MSP). Upon activation, Ron is able to induce cell dissociation, migration and matrix invasion. Exon 11 skipping of Ron pre-mRNA produces Ron△165 protein that is constitutively active even in the absence of its ligand. Here we show that knockdown of SRSF2 promotes the decrease of exon 11 inclusion, whereas overexpression of SRSF2 promotes exon 11 inclusion. We demonstrate that SRSF2 promotes exon 11 inclusion through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…It has been demonstrated in a previous study that mutations in minigenes can affect the splicing of alternative exons (12). The results of the present study confirmed that the differential location of PTCs on alternative exons 5 and 6 may induce NMD of the majority of the spliced or partially spliced exon isoforms.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It has been demonstrated in a previous study that mutations in minigenes can affect the splicing of alternative exons (12). The results of the present study confirmed that the differential location of PTCs on alternative exons 5 and 6 may induce NMD of the majority of the spliced or partially spliced exon isoforms.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have demonstrated that serine/arginine-rich splicing factor (SRSF) 1 and heterogeneous nuclear ribonucleoprotein A1 regulate the epithelial-to-mesenchymal transition through the regulation of exon 11 alternative splicing in RON pre-mRNA (10,11). Our previous study also identified SRSF2 as an important regulator protein for the alternative splicing of exon 11 (12). Another isoform, RONΔ160, is produced by the exclusion of exons 5 and 6 and lacks the first immunoglobulin-plexin-transcription domain in the extracellular β chain, and therefore induces cellular transformation, metastasis and protects tumor cells from apoptosis (13)(14)(15).…”
Section: Introductionmentioning
confidence: 93%
“…This is the case of NUMB, for which the reversal of the splicing change induced by RBM10 mutations in lung cancer cells can revert the proliferative phenotype (Bechara et al 2013). Events that contribute to cancer are often controlled by multiple factors, like the exon skipping event of MST1R involved in cell invasion, which is controlled by SRSF1 (Ghigna et al 2005), HNRNPA2B1 (Golan-Gerstl et al 2011), HNRNPH1, and SRSF2 (Moon et al 2014). Furthermore, some events may be affected by both mutations and expression changes in splicing factors.…”
mentioning
confidence: 99%
“…This is the case of NUMB, for which the reversal of the splicing change induced by RBM10 mutations in lung cancer cells can revert the proliferative phenotype (Bechara et al 2013). Events that contribute to cancer are often controlled by multiple factors, like the exon skipping event of MST1R involved in cell invasion, which is controlled by SRSF1 (Ghigna et al 2005), HNRNPA2B1 (Golan-Gerstl et al 2011), HNRNPH1 and SRSF2 (Moon et al 2014). Furthermore, some events may be affected by both mutations and expression changes in splicing factors.…”
Section: Introductionmentioning
confidence: 99%
“…A similar example is S6K1, where expression of isoform-2 is sufficient to reverse the transformation of immortal rodent fibroblasts caused by the overexpression of SRSF1 in vitro and in vivo 9 . Events that contribute to cancer are often controlled by multiple factors, like the exon skipping event of MST1R involved in cell invasion, which is controlled by SRSF1 15 , hnRNPA2B1 12 , hnRNPH1 and SRSF2 16 . Furthermore, some events may be affected by both mutations and expression changes in splicing factors.…”
Section: Introductionmentioning
confidence: 99%